2016
DOI: 10.1158/1940-6207.capr-15-0315
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid Differentiation Factor 88 Signaling in Bone Marrow–Derived Cells Promotes Gastric Tumorigenesis by Generation of Inflammatory Microenvironment

Abstract: It has been established that COX-2 and downstream signaling by prostaglandin E 2 (PGE 2 ) play a key role in tumorigenesis through generation of inflammatory microenvironment. Tolllike receptor (TLR) signaling through myeloid differentiation factor 88 (MyD88) also regulates inflammatory responses in tumors. However, the relationship between these distinct pathways in tumorigenesis is not yet fully understood. We herein investigated the role of MyD88 in gastric tumorigenesis using Gan mice, which develop inflam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…Innate immune responses through the TLRs have also been shown to be involved in tumor promotion . We have shown that the COX‐2/PGE 2 pathway triggers generation of inflammatory microenvironment in the stomach in a mouse gastric tumor model, and that TLR signaling through the adaptor molecule MyD88 is required for COX‐2/PGE 2 ‐induced gastritis and gastric tumor development . Accordingly, it is possible that the interplay of the COX‐2/PGE 2 and TLR/MyD88 pathways is important for generation of the inflammatory microenvironment, which promotes tumorigenesis.…”
mentioning
confidence: 98%
“…Innate immune responses through the TLRs have also been shown to be involved in tumor promotion . We have shown that the COX‐2/PGE 2 pathway triggers generation of inflammatory microenvironment in the stomach in a mouse gastric tumor model, and that TLR signaling through the adaptor molecule MyD88 is required for COX‐2/PGE 2 ‐induced gastritis and gastric tumor development . Accordingly, it is possible that the interplay of the COX‐2/PGE 2 and TLR/MyD88 pathways is important for generation of the inflammatory microenvironment, which promotes tumorigenesis.…”
mentioning
confidence: 98%
“…Mice were maintained on a mixed background. Tamoxifen (Sigma-Aldrich) was injected intraperitoneally in mice using both "high-dose" and "low-dose" protocols that have been extensively vetted previously by our laboratory and others (Huh et al , 2012Capoccia et al 2013;Khurana et al 2013;Maeda et al 2016;Saenz et al 2016). Doses of 5 mg per 20 g of mouse body weight ("high-dose") delivered on three consecutive days cause the death of >90% of PCs within 4 d of the initial dose followed by recovery to a full complement of PCs by 3 wk.…”
Section: Creert2mentioning
confidence: 99%
“…2) (30). Besides these, innate immune responses through the TLR/MyD88 adapter signaling also play a role in tumorigenesis (31,32). In fact, it has been shown that almost all the gastric tumors show an induction of COX-2 expression (33) and H. pylori infection is known to lead to COX-2 induction (34).…”
Section: Inflammatory Response To H Pylori Infectionmentioning
confidence: 99%